CNA quiet day curves and their sidereal time dependence - Araki, Takashi; Sato, Natsuo (National Institute of Polar Research, 1991)
P(論文) This paper presents a method of obtaining a riometer quiet day curve (QDC) of the correct shape, after modifying the technique of inflection point method proposed by R.J. ARMSTRONG et al. (Planet. Space Sci., 25,1193,1977) with Fourier analysis using computer assisted programing of the data. This method was applied to 30MHz riometer data observed at Tjornes (from 8 September 1984 to 30 September 1986) and Husafell (from 15 August 1985 to 31 August 1986) in Iceland. The QDCs are usefull in studying the diurnal, seasonal and solar cycle variations of average ionospheric absorption level. departmental bulletin paper